Development of PowerPoint-Based Interactive Learning Media to Improve Learning Outcomes of Fifth Grade Students of SD Negeri 4 Bandar Baru - Novitasari, Eka; Atina (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to develop an interactive PowerPoint-based learning media that is feasible and effective in improving the learning outcomes of fifth-grade students at SD Negeri 4 Bandar Baru. The background of this research stems from the low learning outcomes caused by the use of conventional and less engaging learning media. This research employs a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 30 fifth-grade students from SD Negeri 4 Bandar Baru. Data were collected through validation questionnaires from material, media, and language experts, as well as student learning achievement tests. Data analysis employed both qualitative and quantitative descriptive techniques. The results indicated that the interactive PowerPoint-based learning media developed in this study obtained a very feasible rating from experts, with an average validation score of 92%. Field trials revealed that the use of this media effectively improved student learning outcomes, as shown by an increase in the average score from 68.5 (pretest) to 85.2 (posttest). Furthermore, students demonstrated greater interest and motivation during the learning process. Therefore, the interactive PowerPoint-based learning media is declared feasible, practical, and effective to be used in the learning process for fifth-grade students at SD Negeri 4 Bandar Baru.